Manajemen transisi kurikulum 2013 menuju kurikulum merdeka di SD Negeri Pandeyan Yogyakarta - Resmiyati, Resmiyati; Ringko, Fitri Mela; Pramesti, Rahmadhita; Zasilaturrohmah, Dwi Evrilia; Tallo, Maria Desti Bui; Alfriansyah, Adhitya; Prasanti, Arista Nida; Rachmadhani, Nisakurin; Wahyuni, Dini (Indonesian Journal of Educational Management and Leadership, 2024)
Purpose − The aims of this research are (1) to describe the preparations of SD N Pandeyan in implementing the Independent Curriculum, (2) to describe the steps for implementing the 2013 Curriculum to the Independent Curriculum at SD N Pandeyan, (3) to describe the challenges and obstacles at SD N Pandeyan which has implemented Independent Curriculum. Method − This research is qualitative research with a case study approach, with interviews as a data collection technique. The data source in this research is the Principal of SD N Pandeyan. The data analysis technique uses an interactive data analysis technique which consists of data collection, data display, conclusion: drawing/verifying, and data condensation. Findings − The research results show that one of the preparations that needs to be done is training educators, especially class I and IV teachers. Meanwhile, the steps for implementing the Independent Curriculum are carried out by combining it with the previous curriculum, and the Independent Curriculum emphasizes character education, not just mastery of knowledge. In implementing the Independent Curriculum, of course several challenges and obstacles arise, such as the need to learn a lot from various sources that have been provided, such as when training/workshops are held.